Assessing the resilience of Mediterranean holm oaks to disturbances using selective thinning - López, Bernat C.; Gracia, Carlos a; SABATE, Santiago; KEENAN, Trevor (Acta Oecologica, 2009)
Climate change will increase the frequency and the intensity of droughts in the Mediterranean region, likely reducing growth and increasing mortality of holm oaks (Quercus ilex), one of the most abundant species of Mediterranean forests. In water-limited systems such as those of the Mediterranean, carbon allocation patterns strongly favour belowground accumulation, especially in large subterranean structures called lignotubers. The resilience of these forests depends largely on the replenishment rate of these carbon reserves after disturbances. An experimental thinning, with two intensities (removal of 40% and 80% of basal area), was performed in 1992 in a holm oak forest at the Prades Experimental Complex of Catchments (NE Spain). In 2002, a second thinning was carried out in subplots within the former experimental 0.5 ha plots. Samples from the lignotubers of holm oak trees were analyzed for starch, and both mobile and immobile chemical components, in order to assess the resilience of holm oaks to repeated disturbances. Our results show that after 10 years, starch stocks in the lignotubers have only recovered to half their former values. Removing 40% of the basal area instead of 80% is suggested to be the better managing option for this kind of forests.
Keywords: mediterranean forest; NIRS; Quercus ilex; resilience; resprouting; starch; thinning

Canopy nutrient content of a Quercus ilex L. forest: fertilization and irrigation effects - SABATE, Santiago; Gracia, Carlos a; Ecology, Forest; Barcelona, Universitat De (Forest Ecology and Management, 1994)
A multifactorial ANOVA experiment was designed for a Quercus ilex L. forest at the Prades Experimental Complex of Catchments in Tarragona (northeast Spain). The purpose of this study was to clarify the relative importance of water, nitrogen and phosphorus as factors controlling primary production. Eight plots comprising all possible combinations of the three factors (including a control) were laid out in three replicate blocks. Fertilizers were applied in March 1989 (125 kg ha−1 P, 250 kg ha−1 N). Irrigation was applied at a rate of 20 mm week−1 during the warm season. Nitrogen and phosphorus contents and their distribution in leaves and stems as a response to the experiment are presented in this paper. These variables as well as the structural characteristics were selected because they are among the most dynamic and should present changes over short time periods following changes in environmental conditions. The values before initial treatments (autumn 1988) and after treatments (summer 1990) were analysed. Results showed that water treatments affect the nutrient content; the lower concentrations found in water treatments may probably be explained as a dilution effect after an increase of production. Nitrogen treatments significantly increase the nitrogen concentration in young leaves while phosphorus treatments do not have significant effect on the phosphorus concentrations. Nevertheless, phosphorus treatment significantly lowers the potassium concentration.
Keywords: Canopy; fertilization; irrigation; nutrient content; Quercus ilex